2005
DOI: 10.1542/peds.2004-0682
|View full text |Cite
|
Sign up to set email alerts
|

Pain Among Children and Adolescents: Restrictions in Daily Living and Triggering Factors

Abstract: ABSTRACT. Objectives. Pain among children and adolescents has been identified as an important public health problem. Most studies evaluating recurrent or chronic pain conditions among children have been limited to descriptions of pain intensity and duration. The effects of pain states and their impact on daily living have rarely been studied. The objective of this study was to investigate the impact of perceived pain on the daily lives and activities of children and adolescents. In addition, we sought to delin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
487
13
39

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 716 publications
(593 citation statements)
references
References 32 publications
42
487
13
39
Order By: Relevance
“…Accordingly, the 51 individuals with LE pain were categorized in the LE+ group and the 124 individuals without LE pain were categorized in the LEÀ group (Table 3). Potentially confounding variables that may influence LE pain group categorization such as age, sex, and Tanner stage were compared between the LE+ and LEÀ groups [25,36,44]. We compared age between the LE+ and LEÀ groups using independent samples t-tests and found the mean age for both groups as approximately 13 years old (Table 3) (t = 0.037, p = 0.970).…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, the 51 individuals with LE pain were categorized in the LE+ group and the 124 individuals without LE pain were categorized in the LEÀ group (Table 3). Potentially confounding variables that may influence LE pain group categorization such as age, sex, and Tanner stage were compared between the LE+ and LEÀ groups [25,36,44]. We compared age between the LE+ and LEÀ groups using independent samples t-tests and found the mean age for both groups as approximately 13 years old (Table 3) (t = 0.037, p = 0.970).…”
Section: Methodsmentioning
confidence: 99%
“…Pain is known to affect daily living activities [11]; thus, to minimize its effect on the ASK score, we conducted the study 2 weeks after immobilization, when the self-reported pain had subsided in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…An Australian study of 207 children and adolescents attending a paediatric pain management clinic found that 95% had missed school, 90% had been unable to participate in some sporting activity and 71% had suffered some sleep disruption (Chalkiadis, 2001). Roth-Isigkeit et al (2005) found that 30-40% of children/adolescents with pain reported effects of their pain on school attendance, hobbies, social contacts, appetite, sleep, as well as increased utilization of health services because of their pain. An understanding of the range and interaction of all these different effects is crucial to the effective recognition and treatment of chronic pain in children.…”
Section: The Impact Of Chronic Pain On Children and Their Familiesmentioning
confidence: 99%